2015
DOI: 10.7567/jjap.54.07hf14
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of scatterer size and acoustic concentration in sound field produced by linear phased array transducer

Abstract: Although there have been several quantitative ultrasound studies on the methods of estimation of scatterer size and acoustic concentration based on the analysis of RF signals for tissue characterization, some problems, e.g., narrow frequency bandwidths and complex sound fields, have limited the clinical applications of such methods. In this report, two types of ultrasound transducer are investigated for the estimation of the scatterer size and acoustic concentration in two glass bead phantoms of different weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…where R is the axial distance from the transducer to the centre of the ROI, D is the active area of the 12 transducer elements, L is the gate length, is the reflectivity coefficient of a water and quartz interface, and is an attenuation compensation function for a gated signal [ 25 ]. Note that, following convention, all lengths were defined in mm.…”
Section: Methodsmentioning
confidence: 99%
“…where R is the axial distance from the transducer to the centre of the ROI, D is the active area of the 12 transducer elements, L is the gate length, is the reflectivity coefficient of a water and quartz interface, and is an attenuation compensation function for a gated signal [ 25 ]. Note that, following convention, all lengths were defined in mm.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, the attenuation of gelatin increased by adding glass beads under a similar ultrasonic frequency. [32][33][34] The tendency of SiO 2 addition was basically the same as with glass bead addition, but SiO 2 nanoparticles would present better stability and dispersion in gelatin phantoms. Burlew et al demonstrated that the addition of barium titanate nanoparticles increased the attenuation of agarose, PAA, and PDMS phantoms.…”
Section: Acoustic Properties Of Soft Tissue Phantomsmentioning
confidence: 99%
“…This method has been applied for the analysis and classification of various tissues, such as, the liver, skin, lymph nodes, and blood. [18][19][20][21][22][23][24][25][26][27] Cloutier et al calculated the backscattering coefficient from the RF signal obtained from the vascular lumen and estimated the attenuation coefficient of tissues and the parameters indicating the structure of the RBC aggregates, [24][25][26] and showed the possibility of monitoring the systemic inflammatory state by in vivo measurements. 27) However, few studies using these methods have involved human subjects, and diagnosis using this method has not been clinically established.…”
Section: Introductionmentioning
confidence: 99%